PENGARUH PENGETAHUAN DAN GAYA HIDUP MAHASISWA TERHADAP MINAT MENGGUNAKAN PINJAMAN ONLINE - Rizqon, Muhammad Fathir; Fadil, Khaidir; Tanjung, Hendri (An Nuqud Journal of Islamic Economics, 2025)
Online loans emerged because technology is increasingly developing to help the national economy and can provide public financial services or what is commonly known as financial technology (fintech). This convenience is what makes students interested in using this online loan service, where generally these students do not have jobs that promise to support their financial abilities and lifestyle. With online loan cases that have occurred in Indonesia, it is proven that the importance of a person's knowledge in making a decision. Likewise, the impact that occurs is whether good or bad. This research aims to determine the knowledge and lifestyle of FAI Sharia Economics students at Ibn Khaldun University, Bogor regarding their interest in using online loans. The method used is descriptive quantitative. The sample used in this research was 70 respondents with a sampling collection technique using a questionnaire. The data analysis technique is multiple linear regression analysis with IBM SPSS version 25. Meanwhile, for online loans, researchers used descriptive analysis based on DSN-MUI. The research results show that students' knowledge and lifestyle on interest in using online loans have a positive and significant effect partially and simultaneously. With the result of this variable being 81.4%, the remainder is influenced by other variables at 18.6%. The conclusion is that UIKA Sharia Economics FAI students have met the criteria regarding online loans